Polyphenylene sulfide composite material as well as preparation method and application thereof

By using a silane coupling agent to modify the collaborative modification method of glass fiber and polymer in polyphenylene sulfide composite materials, the problems of brittleness and friction loss of pure PPS resin are solved, and the mechanical properties and wear resistance of the composite materials are significantly improved.

CN119529532APending Publication Date: 2025-02-28KUNSHAN HEZHENRUIXIN COMPOSITE MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411510103.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Pure polyphenylene sulfide (PPS) resins are limited in their application range due to their inherent brittleness, high friction coefficient and specific wear rate, and the fibers are prone to rupture during extrusion processing, which affects the mechanical properties.

Method used

The collaborative modification method of polyphenylene sulfide, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, glass fiber and silane coupling agent is adopted to modify the binding force and adhesion of the fiber to the matrix by modifying the binding force and adhesion of the fiber to the matrix by silane coupling agent.

Benefits of technology

The mechanical properties and wear resistance of polyphenylene sulfide composites are significantly improved, and the bending strength, tensile strength and notchless impact strength are improved, and the average friction coefficient and wear volume are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105213360000081
    Figure BDA0005105213360000081
  • Figure BDA0005105213360000082
    Figure BDA0005105213360000082
  • Figure BDA0005105213360000091
    Figure BDA0005105213360000091
Patent Text Reader

Abstract

The invention provides a polyphenylene sulfide composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The polyphenylene sulfide composite material provided by the invention is prepared from the following raw materials in parts by mass: 80 to 100 parts of polyphenylene sulfide, 5 to 15 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, 20 to 40 parts of glass fiber and 0.1 to 2 parts of silane coupling agent. According to the invention, the silane coupling agent and the tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer are added to carry out synergistic modification on the polyphenylene sulfide, and the silane part of the coupling agent can generate hydrogen bond combination with active groups on the surfaces of the glass fibers after being hydrolyzed; the organic functional group can be combined with double bonds of the tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, so that the silane coupling agent can be used as a bridge to connect the polymer and fibers, the binding force and cohesiveness of the two phases are enhanced, a better stress transfer effect is achieved, and meanwhile, the crystallization property and wear resistance of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a polyphenylene sulfide composite material and a preparation method and application thereof. Background Art

[0002] Engineering thermoplastic composites have been widely used in engineering fields such as automobiles, aviation and aerospace due to their excellent mechanical and thermal properties, simple processes and reprocessability. Among various engineering thermoplastics, polyphenylene sulfide (PPS) composed of alternating sulfur groups and benzene rings is favored for its excellent thermal properties and chemical resistance. However, the application range of pure PPS resin is greatly limited due to its inherent brittleness and relatively high friction coefficient and specific wear rate. In order to overcome this shortcoming, various high-strength fiber materials (such as carbon fiber, aramid fiber and glass fiber) are often used to reinforce polyphenylene sulfide composites.

[0003] During the extrusion process, the interface between PPS and filler is inert, making it difficult for the filler to disperse in the matrix and thus forming agglomerates. At the same time, the addition of fibers will lead to an increase in melt viscosity, which will cause the fibers to withstand higher shear forces during processing and eventually break, which seriously affects the effect of fiber modification. Therefore, how to improve the performance of fiber-modified PPS is important for its development. Summary of the invention

[0004] The purpose of the present invention is to provide a polyphenylene sulfide composite material and a preparation method and application thereof. The polyphenylene sulfide composite material provided by the present invention has excellent mechanical properties and wear resistance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a polyphenylene sulfide composite material, which comprises the following raw materials by weight: 80-100 parts of polyphenylene sulfide, 5-15 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, 20-40 parts of glass fiber and 0.1-2 parts of silane coupling agent.

[0007] Preferably, the melt index of the polyphenylene sulfide is 200 to 300 g / 10 min.

[0008] Preferably, the diameter of the glass fiber is 9-11 μm, and the length of the glass fiber is 2-4 mm.

[0009] Preferably, the silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane.

[0010] The present invention also provides a method for preparing the polyphenylene sulfide composite material described in the above technical solution, comprising the following steps:

[0011] (1) mixing a silane coupling agent and a hydrolyzate, performing a hydrolysis reaction, adding glass fiber, and performing a modification treatment to obtain a silane coupling agent-modified glass fiber;

[0012] (2) melt-extrude polyphenylene sulfide, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer and the silane coupling agent modified glass fiber obtained in step (1) to obtain a polyphenylene sulfide composite material.

[0013] Preferably, the hydrolyzate in step (1) is a mixture of ethanol and water; the mass ratio of ethanol to water in the hydrolyzate is 1:(9-11).

[0014] Preferably, in step (1), the mass ratio of the silane coupling agent to the hydrolyzate is 1:(9-19).

[0015] Preferably, the temperature of the modification treatment in step (1) is 20 to 30° C., and the time of the modification treatment is 5 to 20 minutes.

[0016] Preferably, the temperature of melt extrusion in step (2) is 300-350°C.

[0017] The present invention also provides the use of the polyphenylene sulfide composite material described in the above technical solution or the polyphenylene sulfide composite material prepared according to the preparation method described in the above technical solution in the fields of automobiles, aviation and aerospace.

[0018] The present invention provides a polyphenylene sulfide composite material, which includes the following raw materials by weight: 80 to 100 parts of polyphenylene sulfide, 5 to 15 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, 20 to 40 parts of glass fiber and 0.1 to 2 parts of silane coupling agent. The silane coupling agent and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer are added to the composite material of the present invention to synergistically modify the polyphenylene sulfide. After the silane part of the coupling agent is hydrolyzed, it can produce hydrogen bonds with the active groups on the surface of the glass fiber, and the organic functional group can be combined with the double bond of the tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, so that the silane coupling agent can be used as a bridge to connect the polymer and the fiber, enhance the bonding force and adhesion of the two phases, play a better stress transfer role, and at the same time improve the crystallization performance of the composite material and improve the wear resistance of the composite material. The results of the embodiment show that the flexural strength, tensile strength and unnotched impact strength of the polyphenylene sulfide composite material provided by the present invention are higher, and the average friction coefficient and wear volume can be reduced to 0.22 and 4.6×10 -3 cm -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a mechanical property diagram of the polyphenylene sulfide composite material in Examples 1 to 4 of the present invention and Comparative Example 1;

[0020] Figure 2 The friction performance diagram of the polyphenylene sulfide composite material in Examples 1 to 4 of the present invention and Comparative Example 1;

[0021] Figure 3 1 is the cooling curve of the polyphenylene sulfide composite material in Examples 1 to 4 of the present invention and Comparative Example 1;

[0022] Figure 4 The secondary heating curves of the polyphenylene sulfide composite materials in Examples 1 to 4 of the present invention and Comparative Example 1;

[0023] Figure 5 is the infrared spectrum of the polyphenylene sulfide composite material in Example 1 of the present invention;

[0024] Figure 6 The SEM images of the impact cross sections of the polyphenylene sulfide composite materials in Examples 1 to 4 of the present invention and Comparative Example 1;

[0025] Figure 7 The SEM images of the friction surfaces of the polyphenylene sulfide composite materials in Examples 1 to 4 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0026] The invention provides a polyphenylene sulfide composite material, which comprises the following raw materials by weight: 80-100 parts of polyphenylene sulfide, 5-15 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, 20-40 parts of glass fiber and 0.1-2 parts of silane coupling agent.

[0027] In parts by weight, the raw materials for preparing the polyphenylene sulfide composite material of the present invention include 80 to 100 parts of polyphenylene sulfide (PPS), preferably 85 to 95 parts, and more preferably 90 parts.

[0028] In the present invention, the melt index (MFR) of the polyphenylene sulfide is preferably 200 to 300 g / 10 min, more preferably 250 g / 10 min. In the present invention, the polyphenylene sulfide is used as a matrix component. The present invention limits the amount and parameters of polyphenylene sulfide to the above range, which can further improve the mechanical properties and wear resistance of the polyphenylene sulfide composite material.

[0029] The present invention has no special limitation on the source of the polyphenylene sulfide, and commercial products known to those skilled in the art can be used. In the embodiment of the present invention, the polyphenylene sulfide comes from Zhejiang Xinhecheng Co., Ltd., model: Xinhecheng 1130c.

[0030] Based on 80 to 100 parts of polyphenylene sulfide, the raw materials for preparing the polyphenylene sulfide composite material of the present invention include 5 to 15 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (THV), preferably 8 to 12 parts, and more preferably 10 parts.

[0031] In the present invention, the tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (THV) and the silane coupling agent modified glass fiber work synergistically to improve the mechanical properties and wear resistance of the polyphenylene sulfide composite material. The present invention limits the amount of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (THV) to the above range, which can further improve the mechanical properties and wear resistance of the polyphenylene sulfide composite material.

[0032] The present invention has no particular limitation on the source of the tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (THV), and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (THV) is from 3M, model: 221GZ.

[0033] Based on 80 to 100 parts by weight of polyphenylene sulfide, the raw materials for preparing the polyphenylene sulfide composite material of the present invention include 20 to 40 parts by weight of glass fiber, preferably 25 to 35 parts by weight, and more preferably 30 parts by weight.

[0034] In the present invention, the diameter of the glass fiber is preferably 9 to 11 μm, more preferably 10 μm; the length of the glass fiber is preferably 2 to 4 mm, more preferably 3 mm. In the present invention, after the glass fiber is modified by a silane coupling agent, it synergizes with THV to improve the mechanical properties and wear resistance of the polyphenylene sulfide composite material. The present invention limits the amount, length and diameter of the glass fiber within the above range, which can further improve the mechanical properties and wear resistance of the polyphenylene sulfide composite material.

[0035] The present invention has no special limitation on the source of the glass fiber, and commercially available products known to those skilled in the art can be used. In the embodiment of the present invention, the glass fiber comes from Taishan Glass Fiber Co., Ltd., model: ECS10-3.0-T443R.

[0036] Based on 80 to 100 parts by weight of polyphenylene sulfide, the raw materials for preparing the polyphenylene sulfide composite material of the present invention include 0.1 to 2 parts of silane coupling agent, preferably 0.5 to 2 parts, and more preferably 1 to 2 parts.

[0037] In the present invention, the silane coupling agent is preferably 3-(isobutylene acyloxy)propyltrimethoxysilane (KH570). The present invention uses a silane coupling agent to modify the glass fiber. The silane part of the coupling agent can produce hydrogen bonds with the active groups on the surface of the glass fiber after hydrolysis, and the organic functional group can be combined with the double bond of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, so that the silane coupling agent can be used as a bridge to connect the polymer and the fiber, enhance the bonding force and adhesion of the two phases, play a better stress transfer role, and improve the mechanical properties and wear resistance of the composite material. The present invention limits the amount and type of the silane coupling agent within the above range, which can further improve the mechanical properties and wear resistance of the polyphenylene sulfide composite material.

[0038] The present invention has no particular limitation on the source of the silane coupling agent, and commercially available products known to those skilled in the art may be used. In an embodiment of the present invention, the silane coupling agent comes from Hubei New Blue Sky New Materials Co., Ltd.

[0039] The present invention adopts THV and silane coupling agent modified glass fiber as the modification system, synergistically modifies PPS resin, controls the amount of each component, improves the mechanical properties of PPS and reduces its friction loss.

[0040] The present invention also provides a method for preparing the polyphenylene sulfide composite material described in the above technical solution, comprising the following steps:

[0041] (1) mixing a silane coupling agent and a hydrolyzate, performing a hydrolysis reaction, adding glass fiber, and performing a modification treatment to obtain a silane coupling agent-modified glass fiber;

[0042] (2) melt-extrude polyphenylene sulfide, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer and the silane coupling agent modified glass fiber obtained in step (1) to obtain a polyphenylene sulfide composite material.

[0043] The invention mixes a silane coupling agent and a hydrolysis solution, performs a hydrolysis reaction, adds glass fiber, performs a modification treatment, and obtains silane coupling agent modified glass fiber.

[0044] In the present invention, the hydrolyzate is preferably a mixture of ethanol and water; the mass ratio of ethanol to water in the hydrolyzate is preferably 1:(9-11), more preferably 1:10.

[0045] In the present invention, the mass ratio of the silane coupling agent to the hydrolyzate is preferably 1:(9-19), more preferably 1:(10-15). The present invention limits the composition of the hydrolyzate and the mass ratio of the silane coupling agent to the hydrolyzate within the above range, so that the silane coupling agent can be fully hydrolyzed, which is more conducive to the reaction with the glass fiber.

[0046] The present invention has no special limitation on the mixing operation of the silane coupling agent and the hydrolyzate, and a technical solution for mixing materials well known to those skilled in the art can be adopted.

[0047] In the present invention, the temperature of the hydrolysis reaction is preferably 20-30°C; the time of the hydrolysis reaction is preferably 10-20 minutes, more preferably 15 minutes; the hydrolysis reaction is preferably carried out under stirring conditions. The present invention has no special restrictions on the stirring method and rate, and the stirring method and rate familiar to those skilled in the art can be used. The present invention limits the temperature and time of the hydrolysis reaction to the above range, so that the silane coupling agent can be fully hydrolyzed.

[0048] In the present invention, the temperature of the modification treatment is preferably 20 to 30°C; the time of the modification treatment is preferably 5 to 20 minutes, more preferably 10 to 15 minutes; the modification treatment is preferably carried out under stirring conditions. The present invention has no special restrictions on the stirring method and rate, and the stirring method and rate well known to those skilled in the art can be used. The present invention limits the temperature and time of the modification treatment within the above range, so that the silane coupling agent can fully react with the glass fiber.

[0049] After the modification treatment is completed, the present invention preferably takes out the modified glass fiber and then dries it to obtain the silane coupling agent modified glass fiber.

[0050] The present invention has no particular limitation on the operation of taking out the modified glass fiber, and the glass fiber can be taken out in a manner well known to those skilled in the art.

[0051] In the present invention, the drying temperature is preferably 90-110° C., more preferably 100° C. The present invention has no particular limitation on the drying time, as long as the hydrolyzate is sufficiently removed.

[0052] After obtaining the silane coupling agent modified glass fiber, the present invention melt-extrudes polyphenylene sulfide, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer and the silane coupling agent modified glass fiber to obtain a polyphenylene sulfide composite material.

[0053] In the present invention, the melt extrusion is preferably carried out in an extruder. The present invention has no particular limitation on the type of the extruder, and any extruder well known to those skilled in the art can be used.

[0054] The present invention preferably mixes polyphenylene sulfide and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer to obtain a mixed material, and then adds the mixed material and silane coupling agent modified glass fiber into the extruder from the main and side feed ports of the extruder respectively.

[0055] In the present invention, the temperature of the melt extrusion is preferably 300-350° C. The present invention controls the feeding position and the melt extrusion temperature, so that the components can be mixed more evenly, and the performance of the polyphenylene sulfide composite material can be further improved.

[0056] After the melt extrusion is completed, the present invention preferably sequentially dries and cools the melt extruded product to obtain a polyphenylene sulfide composite material.

[0057] In the present invention, the drying temperature is preferably 90-110° C., more preferably 100° C.; the drying time is preferably 10-15 h, more preferably 12 h.

[0058] The present invention has no special limitation on the cooling operation, and cooling to room temperature may be performed using cooling technical solutions well known to those skilled in the art.

[0059] The present invention also provides the use of the polyphenylene sulfide composite material described in the above technical solution or the polyphenylene sulfide composite material prepared according to the preparation method described in the above technical solution in the fields of automobiles, aviation and aerospace.

[0060] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well known to those skilled in the art may be adopted.

[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] The polyphenylene sulfide composite material is prepared from the following raw materials by weight: 90 parts of polyphenylene sulfide (Zhejiang Xinhecheng Co., Ltd., model: Xinhecheng 1130c, MFR=250g / 10min, average molecular weight of 40,000), 10 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (Japan 3M Co., Ltd., model: 221GZ), 30 parts of glass fiber (Taishan Glass Fiber Co., Ltd., model: ECS10-3.0-T443R, length of 10μm, diameter of 3mm), 0.4 parts of KH570 silane coupling agent (Hubei Xinlantian New Materials Co., Ltd.) and 4.8 parts of hydrolyzate;

[0064] The preparation method of the polyphenylene sulfide composite material is:

[0065] (1) After weighing glass fiber and KH570 silane coupling agent according to the formula ratio, the silane coupling agent is added to the hydrolyzate, and stirred and hydrolyzed at 25° C. for 15 minutes. The hydrolyzate is prepared by mixing anhydrous ethanol and distilled water in a mass ratio of 1:10, and the mass ratio of KH570 to the hydrolyzate is 1:12. After the hydrolysis is completed, the glass fiber is added, and the modification treatment is carried out at 25° C. for 10 minutes at a stirring speed of 200 rpm. The fiber is taken out and placed in an oven at 100° C. for drying to obtain a silane coupling agent modified glass fiber;

[0066] (2) Weigh polyphenylene sulfide and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (THV) according to the formula, add them into a high-speed mixer and mix them evenly to obtain a mixture, add the mixture and silane coupling agent modified glass fiber into an extruder from the main and side feed ports respectively for melt extrusion granulation (the melt extrusion temperature is 320°C), put the extruded material into an oven at 100°C and dry it for 12 hours, then take it out and cool it to obtain a polyphenylene sulfide composite material.

[0067] Example 2

[0068] The polyphenylene sulfide composite material is prepared from the following raw materials by weight: 90 parts of polyphenylene sulfide (Zhejiang Xinhecheng Co., Ltd., model: Xinhecheng 1130c, MFR=250g / 10min, average molecular weight of 40,000), 10 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (Japan 3M Co., Ltd., model: 221GZ), 30 parts of glass fiber (Taishan Glass Fiber Co., Ltd., model: ECS10-3.0-T443R, length of 10μm, diameter of 3mm), 0.8 parts of KH570 silane coupling agent (Hubei Xinlantian New Materials Co., Ltd.) and 9.6 parts of hydrolyzate;

[0069] The preparation method is the same as Example 1.

[0070] Example 3

[0071] The polyphenylene sulfide composite material is prepared from the following raw materials by weight: 90 parts of polyphenylene sulfide (Zhejiang Xinhecheng Co., Ltd., model: Xinhecheng 1130c, MFR=250g / 10min, average molecular weight of 40,000), 10 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (Japan 3M Co., Ltd., model: 221GZ), 30 parts of glass fiber (Taishan Glass Fiber Co., Ltd., model: ECS10-3.0-T443R, length of 10μm, diameter of 3mm), 1.2 parts of KH570 silane coupling agent (Hubei Xinlantian New Materials Co., Ltd.) and 14.4 parts of hydrolyzate;

[0072] The preparation method is the same as Example 1.

[0073] Example 4

[0074] The polyphenylene sulfide composite material is prepared from the following raw materials by weight: 90 parts of polyphenylene sulfide (Zhejiang Xinhecheng Co., Ltd., model: Xinhecheng 1130c, MFR=250g / 10min, average molecular weight of 40,000), 10 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer (Japan 3M Co., Ltd., model: 221GZ), 30 parts of glass fiber (Taishan Glass Fiber Co., Ltd., model: ECS10-3.0-T443R, length of 10μm, diameter of 3mm), 2.0 parts of KH570 silane coupling agent (Hubei Xinlantian New Materials Co., Ltd.) and 24 parts of hydrolyzate;

[0075] The preparation method is the same as Example 1.

[0076] Comparative Example 1

[0077] The silane coupling agent in Example 1 was omitted, and other parameters were the same as those in Example 1.

[0078] The mechanical properties of the polyphenylene sulfide composite materials in Examples 1 to 4 and Comparative Example 1 were tested.

[0079] Preparation of mechanical properties test specimens: The dried extruded pellets are added into an injection molding machine and injection molded into mechanical properties test specimens.

[0080] Mechanical properties test: The samples were subjected to tensile, bending and unnotched impact strength tests according to GB / T1040.1-2018, GB / T9341-2008 and GB / T1843-2008 standards, with a tensile speed of 10 mm / min, a bending speed of 5 mm / min, and an impact pendulum of 2.75 J. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the flexural strength, tensile strength and unnotched impact strength of the polyphenylene sulfide composite material without coupling agent modification are 116MPa, 81.4MPa and 23kJ / m 2. When the dosage of KH570 is 2 parts, the comprehensive mechanical properties of the composite material are the best. Compared with no coupling agent added, the flexural strength increased by 37.9%, the tensile strength increased by 37.6%, and the unnotched impact strength increased by 52.2%. By comparing the impact strength of the two groups of KH570 1.2 parts and KH570 2.0 parts, it can be seen that the modification effect of the coupling agent becomes gentle, which can indicate that the optimal dosage of the coupling agent is around 2 parts. The above results show that with the increase of KH570 content, the mechanical properties of polyphenylene sulfide composite materials are improved to varying degrees. After the silane part of the coupling agent is hydrolyzed, it can produce hydrogen bonds with the active groups on the surface of the glass fiber, and the organic functional groups can react with the double bond structure of THV in the matrix of the polyphenylene sulfide composite material to couple, so that KH570 can act as a bridge to connect the polymer and the fiber, enhance the binding force and adhesion of the two phases, and play a better stress transfer role.

[0081] The friction properties of the polyphenylene sulfide composite materials in Examples 1 to 4 and Comparative Example 1 were tested.

[0082] Preparation of friction test specimens: The dried extruded pellets were quantitatively placed into a customized molding mold, heated at 330°C in a muffle furnace for 30 min, and then the mold was transferred to a preheated molding machine for molding for 10 min (280°C, 10 MPa, and venting three times). Finally, the mold was transferred to a flat-plate vulcanizer and maintained at a pressure of 5 MPa for 6 min to obtain a rectangular specimen with a size of 30×7×6 mm.

[0083] Friction performance test: According to GB / T 3960-2016 standard, load 20kg, friction time 120min. The results are as follows Figure 2 As shown. Figure 2 It can be seen that with the increase of KH570 dosage, the wear volume and average friction coefficient of polyphenylene sulfide composite materials show an overall downward trend. When the amount of KH570 reaches 2 parts, the average friction coefficient and wear volume reach the minimum value, which are 0.22 and 4.6×10 -3 cm -1 Compared with the case without coupling agent, the wear volume decreased by 50% and the average friction coefficient decreased by 24%. Based on the mechanical properties, 2 parts of KH570 is more suitable for polyphenylene sulfide composites.

[0084] The crystallization properties of the polyphenylene sulfide composite materials in Examples 1 to 4 and Comparative Example 1 were tested.

[0085] DSC test: 5.0mg~10.0mg of polyphenylene sulfide composite material was cut and placed in an aluminum crucible to complete sample preparation. Under the protection of nitrogen atmosphere, the temperature was first increased at 20℃ / min to remove the thermal history, the heating range was: 30℃~330℃, and then the temperature was reduced to 30℃ at a rate of 10℃ / min to obtain a cooling curve, and finally the temperature was increased to 330℃ at a heating rate of 10℃ / min to obtain a secondary heating curve. The DSC data are shown in Table 1. The cooling curve and the secondary heating curve are shown in Table 1. Figures 3-4 shown.

[0086] The crystallinity (X) was calculated according to the DSC test data according to formula (1). c ):

[0087]

[0088] In formula (1), X c is the crystallinity of the sample, %; ΔH c is the crystallization enthalpy of the sample, J / g; ΔH θ is the melting enthalpy (ΔH) of 100% crystalline PPS θ =77.5 J / g); w is the weight content of PPS in the polyphenylene sulfide composite material, %.

[0089] Table 1 DSC data of polyphenylene sulfide composite materials in Examples 1 to 4 and Comparative Example 1

[0090]

[0091]

[0092] from Figures 3-4It can be seen from the DSC curve that when no coupling agent is added, the crystallization peak of the polyphenylene sulfide composite material is wide, and the crystallinity and crystallization temperature are low. This is because the fiber is difficult to disperse inside the matrix, and the agglomeration phenomenon is serious, which hinders the movement and arrangement of the PPS molecular chain, and the molecular chain takes longer to enter the lattice. With the increase of the coupling agent content, the DSC curve of the polyphenylene sulfide composite material shifts, the peak becomes narrower, and the crystallization temperature shows an obvious upward trend. When the KH570 content is 0.4 parts, the crystallization temperature of the polyphenylene sulfide composite material is 233.1℃, and the cooling crystallinity is 59.04%. When the KH570 content is increased to 2 parts, the crystallization temperature of the polyphenylene sulfide composite material increases from 233.1℃ to 236.2℃, and the cooling crystallinity increases from 59.04% to 62.64%. The obvious changes in crystallization temperature and crystallinity confirm the enhancement of the material's crystallization ability. This result shows that the coupling agent improves the compatibility between the fiber and the matrix, giving the fiber a better dispersion effect in the matrix and enhancing its orientation ability during the melt processing. At the same time, the tighter binding force between the modified fiber and the matrix allows the fiber to drive the nearby polymer molecular chains to arrange in order, thereby affecting the crystallization properties of the material.

[0093] The infrared spectrum of the polyphenylene sulfide composite material of test example 1 is as follows: Figure 5 shown.

[0094] FTIR test: prepared by potassium bromide (KBr) tablet method, test range 400~4000cm -1 , resolution 2cm -1 .

[0095] from Figure 5 As can be seen in the figure, 1572cm -1 、1466cm -1 、1387cm -1 The peak at 1090cm is the stretching vibration absorption of the benzene ring skeleton. -1 The peak at 806 cm is the tensile vibration absorption of CS. -1 The strong absorption peak is the characteristic peak of the disubstituted benzene ring at 1214 cm -1 The broad peak near the THV is speculated to be the characteristic absorption peak of the CF bond in THV. Compared with the infrared spectrum of the polyphenylene sulfide composite material, the composite material modified by KH570 has a peak at 1695 cm -1 A new strong peak is prominent at 3418cm -1 A new broad peak at 1695 cm -1 The position is the absorption peak of the C=C bond of the methacryloyloxy group in KH570, 3418 cm -1 The positions correspond to the stretching vibration peaks of OH bonds. The appearance of these new absorption peaks proves the successful introduction of coupling agent KH570.

[0096] The specimens of the polyphenylene sulfide composite materials of Examples 1 to 4 and Comparative Example 1 after impact fracture were selected, and the impact fracture surfaces were subjected to gold spraying treatment and then observed using a scanning electron microscope. The obtained SEM images are as follows: Figure 6 As shown, (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, (d) is Example 3, and (e) is Example 4. Figure 6 It can be seen that with the increase in the amount of KH570, the PPS matrix begins to adhere to the surface of the glass fiber, the gap between the fiber and the matrix decreases and disappears, and more and more polymer matrix remains on the fiber. It proves that the impregnation effect between the glass fiber and the PPS matrix is ​​significantly enhanced, the compatibility and bonding force are significantly improved, the stress on the matrix can be more effectively transferred to the fiber, and the mechanical properties of the polyphenylene sulfide composite material are therefore improved.

[0097] The friction surfaces of the polyphenylene sulfide composite materials of Examples 1 to 4 and Comparative Example 1 were observed using a scanning electron microscope, and the obtained SEM images are as follows: Figure 7 As shown, (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, (d) is Example 3, and (e) is Example 4. Figure 7 It can be clearly seen in (a) that there are a large number of rectangular pits and furrows parallel to the friction direction on the friction surface of the polyphenylene sulfide composite material without adding coupling agent, indicating that the wear mechanism of the polyphenylene sulfide composite material at this time is mainly abrasive wear. Some fibers fall off from the matrix during the friction process, forming hard abrasives between the friction pair and the polyphenylene sulfide composite material, which increases the friction coefficient and wear amount of the polyphenylene sulfide composite material. Figure 7From (b) to (e), when the dosage of KH570 is 0.4 parts, the number of rectangular pits on the friction surface of the polyphenylene sulfide composite material due to fiber debonding is reduced, but cracks and furrows still exist on the surface of the polyphenylene sulfide composite material, and the wear mechanism is still dominated by abrasive wear, which shows that a small amount of coupling agent is not enough to build a strong bond between the fiber and the matrix, and the fiber debonding phenomenon still exists. When the dosage of KH570 is 0.8 parts, the furrows on the wear surface become shallower and the fiber debonding phenomenon basically disappears, replaced by a large amount of polymer flakes. At this time, the fiber has poor dispersion, and the skeleton structure has not yet formed in the matrix, and the cyclic stress applied by the friction pair to the polymer matrix cannot be smoothly transferred. This eventually leads to the diffusion of microcracks in the polyphenylene sulfide composite material, the occurrence of lamellar shedding, and the wear mechanism is transformed into fatigue wear. With the continued increase in the dosage of KH570, the friction surface of the polyphenylene sulfide composite material becomes smoother and smoother, the fiber debonding phenomenon and polymer crushing phenomenon become less and less, and the wear mechanism eventually turns into adhesive wear. This shows that the addition of KH570 strengthens the bonding between the polymer and the glass fiber, making it difficult for the fiber to be pulled out under external force, and reducing the appearance of hard three-body abrasives. At the same time, the fiber can form a solid skeleton in the matrix to replace the matrix to bear the friction load, which plays a role in preventing the matrix from producing large-area flake damage and generating a stable transfer film, thereby showing better wear resistance, which is consistent with the trend of the results shown in the friction test.

[0098] In summary, the polyphenylene sulfide composite material provided by the present invention has excellent mechanical properties and wear resistance.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polyphenylene sulfide composite material, comprising the following raw materials, by weight: 80-100 parts of polyphenylene sulfide, 5-15 parts of tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer, 20-40 parts of glass fiber and 0.1-2 parts of silane coupling agent.

2. The polyphenylene sulfide composite material according to claim 1, characterized in that: The melt index of the polyphenylene sulfide is 200-300 g / 10 min.

3. The polyphenylene sulfide composite material according to claim 1, characterized in that: The diameter of the glass fiber is 9-11 μm, and the length of the glass fiber is 2-4 mm.

4. The polyphenylene sulfide composite material according to claim 1, characterized in that: The silane coupling agent is 3-(isomethacryloyloxy)propyltrimethoxysilane.

5. The method for preparing the polyphenylene sulfide composite material according to any one of claims 1 to 4, comprising the following steps: (1) mixing a silane coupling agent and a hydrolyzate, performing a hydrolysis reaction, adding glass fiber, and performing a modification treatment to obtain a silane coupling agent-modified glass fiber; (2) melt-extrude polyphenylene sulfide, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride polymer and the silane coupling agent modified glass fiber obtained in step (1) to obtain a polyphenylene sulfide composite material.

6. The preparation method according to claim 5, characterized in that: The hydrolyzate in step (1) is a mixture of ethanol and water; the mass ratio of ethanol to water in the hydrolyzate is 1:(9-11).

7. The preparation method according to claim 6, characterized in that: In the step (1), the mass ratio of the silane coupling agent to the hydrolyzate is 1:(9-19).

8. The preparation method according to claim 5, characterized in that: The temperature of the modification treatment in step (1) is 20 to 30° C., and the time of the modification treatment is 5 to 20 minutes.

9. The preparation method according to claim 5, characterized in that: The temperature of melt extrusion in step (2) is 300-350°C.

10. Use of the polyphenylene sulfide composite material according to any one of claims 1 to 4 or the polyphenylene sulfide composite material prepared by the preparation method according to any one of claims 5 to 9 in the fields of automobiles, aviation and aerospace.

Citation Information

Patent Citations

  • High-crystallinity polyphenylene sulfide composite material easy for machining shaping, preparation method and application thereof

    CN110903650A

  • Wear-resistant and impact-resistant PPS / THV hybrid fiber alloy material and preparation method thereof

    CN116285353A

  • Polyphenylene sulfide thermoplastic resin composition

    CN1882658A